2013
DOI: 10.3917/rsg.259.0053
|View full text |Cite
|
Sign up to set email alerts
|

Capital social et accès des PME africaines au crédit bancaire : le cas du Cameroun

Abstract: Dans la plupart des pays d’Afrique Subsaharienne et plus particulièrement au Cameroun, le faible accès aux ressources financières et tout particulièrement au crédit bancaire constitue l’une des contraintes majeures au développement et à la croissance des PME, notamment en raison de la forte asymétrie d’information entre banquiers et petits entrepreneurs. En effet, non seulement ces entreprises sont caractérisées par une certaine opacité dans leur gestion, mais aussi elles sont généralement incapables de présen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…In a different context, such as that of Africa in general and Cameroon in particular; SMEs meet serious obstacles in obtaining bank financing (Kenfack, 2016). Such a problematic have led in recent years researchers (Ngoa & Niyonsaba, 2013;Wamba, 2013;Feudjo & Tchankam, 2013. ) and the Cameroonian government to think of new mechanisms to induce the trust of banks on local firms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different context, such as that of Africa in general and Cameroon in particular; SMEs meet serious obstacles in obtaining bank financing (Kenfack, 2016). Such a problematic have led in recent years researchers (Ngoa & Niyonsaba, 2013;Wamba, 2013;Feudjo & Tchankam, 2013. ) and the Cameroonian government to think of new mechanisms to induce the trust of banks on local firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Cameroon the result of Wanda (2007) revealed that banks have excess liquidity, but they are reluctant to grant loans to SMEs. However, the challenges SMEs encounter to access bank credit are sought to stem from demand-side, supply-side and country-specific factors (Owusu et al, 2015;Chimucheka & Rungani, 2013;Tsambou et al, 2015;Nguena, 2014;Wamba, 2013;Ngongang, 2012;Nguena, 2014;Lopez-Gracia & Aybar-Arias, 2000). Basically, the difficulties face by SMEs to access bank loans is caused by serious problem of information asymmetry (Stiglitz & Weiss, 1981).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dans le contexte camerounais, Wamba () montrent que les promoteurs des PME hésitent à dévoiler l'ensemble des informations dont ils disposent concernant leur entreprise, que ce soit pour des raisons fiscales, concurrentielles ou liées aux coÛts qu'engendre leur production ou simplement par ignorance ou manque de compétences. Très récemment, certains auteurs (Williams, ; Tsambou et al ., ; Nguena et Tsafack, ) ont montré que cette insuffisance d'information est due à la petite taille et le peu de notoriété de la plupart des PME.…”
Section: Revue De La Littératureunclassified
“…Access to finance underpins business start-ups and growth, and creates the employment and wealth needed by the country. Note that an overall reading of the results of Feudjo and Tchankam (2012), Wamba (2013) and Nguena (2013) stipulate that a small proportion of entities in Cameroon (on average 20%) obtain bank credit. The rationale for this study therefore is to find out why only limited SMEs have access to credit.…”
Section: Introductionmentioning
confidence: 99%